Study on relationships between static mechanical properties and composition of low modulus CA mortar. (8th March 2021) - Zeng, Xiaohui; Zhu, Huasheng; Lan, Xuli; Umar, H.A.; Xie, Youjun; Long, Guangcheng
Highlights: Study the relationship between mechanical properties and composition of CA mortar. A mechanical model of CA mortar from four different levels was proposed based on experimental results and theoris. The asphalt has a limited contribution to the static compressive strength f and elastic modulus ECA of the CA mortar. Abstract: As an organic–inorganic composite material, the mechanical properties of cement asphalt mortar (CA mortar) are closely related to its composition. In order to studying the relationship between mechanical properties and composition of CA mortar, a mechanical model of CA mortar from four different levels (i.e., cement hydration products, cement gel skeleton, cement-asphalt composite system and CA mortar) was proposed based on the microscopic experimental results, the gel-space ratio theory and the Hashin composite ball model. The mathematical relationships among the elastic modulus of CA mortar, compressive strength f and composition parameters were derived. The results shown: The volume fraction of cement hydrates is an important parameter affecting the CA mortar elastic modulus ECA and the compressive strength f . When the asphalt is regarded as a pore or a low modulus phase, the static elastic modulus of the CA mortar ECA and the volume fraction of cement hydrates VCH, the compressive strength f and gel-space ratio x all have a power function relationship, and R 2  > 0.7. The cement hydrates in the CA mortar are still a continuous phase and constitutes the composite gel skeleton, asphalt interspersing among them, and the contribution of asphalt to the CA mortar strength and elastic modulus is relatively limited.